Arctic Amplification of Global Warming Strengthened by Sunlight Oxidation of Permafrost Carbon to CO2. Issue 12 (23rd June 2020) - Bowen, J. C.; Ward, C. P.; Kling, G. W.; Cory, R. M.
Abstract: Once thawed, up to 15% of the ∼1, 000 Pg of organic carbon (C) in arctic permafrost soils may be oxidized to carbon dioxide (CO2 ) by 2, 100, amplifying climate change. However, predictions of this amplification strength ignore the oxidation of permafrost C to CO2 in surface waters (photomineralization). We characterized the wavelength dependence of permafrost dissolved organic carbon (DOC) photomineralization and demonstrate that iron catalyzes photomineralization of old DOC (4, 000–6, 300 a BP) derived from soil lignin and tannin. Rates of CO2 production from photomineralization of permafrost DOC are twofold higher than for modern DOC. Given that model predictions of future net loss of ecosystem C from thawing permafrost do not include the loss of CO2 to the atmosphere from DOC photomineralization, current predictions of an average of 208 Pg C loss by 2, 299 may be too low by 14%. Plain Language Summary: The thawing of organic carbon stored in arctic permafrost soils, and its oxidation to carbon dioxide (a greenhouse gas), is predicted to be a major, positive feedback on global warming. However, current estimates of the magnitude of this feedback do not include the oxidation of permafrost soil organic carbon flushed to sunlit lakes and rivers. Here we show that ancient dissolved organic carbon (>4, 000 years old) draining permafrost soils is readily oxidized to carbon dioxide by sunlight. As a consequence, current estimates of additional global warming from the permafrost carbon feedback are too low. Key Points: Wavelength dependence of permafrost dissolved organic carbon (DOC) photomineralization revealed a high lability to visible light Iron catalyzes the photomineralization of old permafrost DOC (>4, 000 a BP) derived from soil lignin and tannin to carbon dioxide (CO2 ) Photomineralization rates of permafrost DOC to CO2 are double that of modern DOC, which will increase future arctic amplification